Lichens and associated fungi from Glacier Bay National Park, Alaska. (March 2020) - Spribille, Toby; Fryday, Alan M.; Pérez-Ortega, Sergio; Svensson, Måns; Tønsberg, Tor; Ekman, Stefan; Holien, Håkon; Resl, Philipp; Schneider, Kevin; Stabentheiner, Edith; Thüs, Holger; Vondrák, Jan; et al.
Abstract: Lichens are widely acknowledged to be a key component of high latitude ecosystems. However, the time investment needed for full inventories and the lack of taxonomic identification resources for crustose lichen and lichenicolous fungal diversity have hampered efforts to fully gauge the depth of species richness in these ecosystems. Using a combination of classical field inventory and extensive deployment of chemical and molecular analysis, we assessed the diversity of lichens and associated fungi in Glacier Bay National Park, Alaska (USA), a mixed landscape of coastal boreal rainforest and early successional low elevation habitats deglaciated after the Little Ice Age. We collected nearly 5000 specimens and found a total of 947 taxa, including 831 taxa of lichen-forming and 96 taxa of lichenicolous fungi together with 20 taxa of saprotrophic fungi typically included in lichen studies. A total of 98 species (10.3% of those detected) could not be assigned to known species and of those, two genera and 27 species are described here as new to science: Atrophysma cyanomelanos gen. et sp. nov., Bacidina circumpulla, Biatora marmorea, Carneothele sphagnicola gen. et sp. nov., Cirrenalia lichenicola, Corticifraga nephromatis, Fuscidea muskeg, Fuscopannaria dillmaniae, Halecania athallina, Hydropunctaria alaskana, Lambiella aliphatica, Lecania hydrophobica, Lecanora viridipruinosa, Lecidea griseomarginata, L. streveleri, Miriquidica gyrizans, Niesslia peltigerae, Ochrolechia cooperi, Placynthium glaciale, Porpidia seakensis, Rhizocarpon haidense, Sagiolechia phaeospora, Sclerococcum fissurinae, Spilonema maritimum, Thelocarpon immersum, Toensbergia blastidiata and Xenonectriella nephromatis . An additional 71 'known unknown' species are cursorily described. Four new combinations are made: Lepra subvelata (G. K. Merr.) T. Sprib., Ochrolechia minuta (Degel.) T. Sprib., Steineropsis laceratula (Hue) T. Sprib. & Ekman and Toensbergia geminipara (Th. Fr.) T. Sprib. & Resl. Thirty-eight taxa are new to North America and 93 additional taxa new to Alaska. We use four to eight DNA loci to validate the placement of ten of the new species in the orders Baeomycetales, Ostropales, Lecanorales, Peltigerales, Pertusariales and the broader class Lecanoromycetes with maximum likelihood analyses. We present a total of 280 new fungal DNA sequences. The lichen inventory from Glacier Bay National Park represents the second largest number of lichens and associated fungi documented from an area of comparable size and the largest to date in North America. Coming from almost 60°N, these results again underline the potential for high lichen diversity in high latitude ecosystems.